2012
DOI: 10.1039/c2cy20218b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic decoloration of methyl orange solution by nanoporous metals

Abstract: Nanoporous Au exhibit catalytic degradation of methyl orange (MO) solution while counterpart bulk Au does not. Other nanoporous metals such as Pd and Ni also exhibited the catalytic MO degradation. Because the degradation occurred under dark conditions, it is clearly distinguished from photocatalytic degradation conventionally observed in TiO2 and ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
3
18
1
Order By: Relevance
“…Kamal et al reported that the CR reduction reaction proceeded with a rate constant of 0.2683 min -1 using copper nanoparticles-chitosan coated filter paper catalyst [47]. Similarly, a rate constants of 0.3308, 1.7 × 10 −3 s −1 , 0.559 and 2.1 × 10 −3 were reported for Co-Cu/ZnPC-Chitosan nanocomposite [21], gold nanoparticles synthesized using 5,7-dihydroxy-6-metoxy-3ʹ,4ʹ methylenedioxyisoflavone (Dalspinin) obtained from Dalbergiacoromandeliana roots [55], Ag and Pt Nanoparticles [56], and nanoporous gold [57]. The extra high values of the rate constants in some of those reports were due to the extremely small particle size of their catalyst.…”
Section: Resultsmentioning
confidence: 71%
“…Kamal et al reported that the CR reduction reaction proceeded with a rate constant of 0.2683 min -1 using copper nanoparticles-chitosan coated filter paper catalyst [47]. Similarly, a rate constants of 0.3308, 1.7 × 10 −3 s −1 , 0.559 and 2.1 × 10 −3 were reported for Co-Cu/ZnPC-Chitosan nanocomposite [21], gold nanoparticles synthesized using 5,7-dihydroxy-6-metoxy-3ʹ,4ʹ methylenedioxyisoflavone (Dalspinin) obtained from Dalbergiacoromandeliana roots [55], Ag and Pt Nanoparticles [56], and nanoporous gold [57]. The extra high values of the rate constants in some of those reports were due to the extremely small particle size of their catalyst.…”
Section: Resultsmentioning
confidence: 71%
“…[10][11][12][13][14] Several methods have been recognized to decolorize or detoxify these dye stuffs such as adsorption, degradation, oxidation and catalytic reduction, which have advantages and disadvantages due to safety issues or energy cost. [15][16][17][18] However, one of the most commonly employed technique is the chemical reduction using reducing agent such as sodium borohydride, hydrazine hydrate, tannic acid, etc. [19][20] Metal nanoparticles show a different behaviour in their physiochemical properties like electrical, [21] optical, [22] and catalytic [23] properties compared to their bulk counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of methyl orange in the solution as a function of soaking time was measured by monitoring the absorbance of the methyl orange at its absorption maximum wavelength ( max = 466.5 nm) using a UVVis spectrometer (UV-2100 Shimadzu, Japan). For comparison with the decoloration by nanoporous Au, 12) reacted amount of methyl orange was normalized by the surface area of the nanodendritic and nanoporous Au, which was estimated by the CV measurements.…”
Section: Decoloration Capacity Of Nanodendritic Aumentioning
confidence: 99%